James, Lloyd. Interview with James Lloyd and his band, and some songs in Bryant's Cove. - Reid, Linda (2005)
James Lloyd talks about playing music with his grandchildren, his friend, and his wife. James talks about how they have played music together for almost two years. Some music is recorded and the interview ended with the song 'This is my homeland.' 00:06- 01:23 introducing James videotaping arrangement of his music band and all participants in his band, they are playing together for almost two years, they play mostly newfoundland songs, James and his grandchildren play music together, they play guitar, accordion, keyboard, qchord, James have four grandchildren who play music with him; 01:25-03:04- play the first tune together; 03:30- 05:34 play the second music together; 05:57- 09:13 James grandchildren play the song ‘this is my land’ altogether; 09:17-10:53 play another music together; 10:55- 23:09 all of them play another song together; 23:52-27:32 played the last song ‘this is my homeland’; 27:36- end of the interview.